Confirmatory factoral validity of public housing satisfaction constructs - Bala Ishiyaku; Rozilah Kasim; Adamu Isa Harir (Cogent Business & Management, 2017)
Validation of housing satisfaction constructs using different perspectives is necessary with increasing relevance of Modelling in post occupancy evaluation (POE). This paper used building components theory to identify tangible and intangible building features and assess the factorial validity of the constructs, with the intention to create substantial and reliable measurement models which can efficiently measure occupants' satisfaction constructs in public housing evaluation. A total of 300 questionnaires were administered in Gombe metropolis, Nigeria. Some 246 were collected, and 212 were used for final analysis after data screening. Tangible and intangible building satisfaction constructs were produced as independent latent constructs while building component satisfaction as the dependent latent construct. The validity of the constructs was confirmed by AMOS software. Results demonstrated the factorability of occupants' satisfaction using building components, tangible and intangible features, and provided a standard for a holistic understanding of building satisfaction components. Hence, this supports the use of building component theory in POE studies. Future studies can identify the relationship between dependent and independent building satisfaction construct. Findings are useful for performance evaluation in public housing studies, Users' satisfaction analyses and formulation of policies to achieve public housing satisfaction.
Keywords: 650